Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XI - Putri, Khairunnisa; Hasratuddin, Hasratuddin (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the improvement in mathematics learning outcomes of class This type of research is PTK which is carried out in two cycles. The subjects in this research were 31 students in class XI MIPA at R.A Kartini Private High School, Tebing Tinggi City. The instruments in this research consisted of tests and observation sheets. The results of data analysis in cycle I obtained an average class percentage of 74.51% and experienced an increase in cycle II, namely obtaining an average class percentage of 85.80%. And the results of the classical completeness analysis in cycle I got a percentage of 70.97%, namely there were 22 students who had reached the KKM, then classical completeness in cycle II got a percentage of 87.09%, namely there were 27 students who had reached the KKM. From this data, it can be seen that there was an increase in diagnostic tests, cycle I tests, and cycle II tests. The observation results indicate that the learning process using the Two Stay Two Stray type cooperative learning model is classified in the good category with a score of 3.31. Based on these data, the indicators for this research have been fulfilled. It was concluded that the application of the Two Stay Two Stray type cooperative learning model could improve the mathematics learning outcomes of class XI MIPA students at R.A Kartini Private High School, Tebing Tinggi City.